A capacidade político-relacional da gestão municipal na implementação do Programa João Pessoa Sustentável - Ramelli, Felipe Leonardo Assis (2023)
Based on the analysis of the João Pessoa Sustentavel Program, this case study aims to investigate how governments can, or cannot, develop political-relational capacities to implement policies in a complex institutional arrangement, marked by the influence of the guidelines of multilateral financial institution. Result of cooperation between João Pessoa City Hall and the Inter-American Development Bank (IDB), the program will promote the resettlement of 800 families living in risk areas in eight communities – Brasília de Palha, Cafofo/Liberdade, Miramar, Tito Silva, Hildon Bandeira, Vila Tambauzinho, Santa Clara and São Rafael. Once its object of study is a policy permeated by conflicts common to large urban projects, the research seeks to infer whether municipal management has developed politicalrelational capacities (PIRES; GOMIDE, 2016) due to creation of a new institutional arrangement for the implementation of actions. In this context, in dialogue with the national and international debate on state capabilities and governance, the work investigated the instruments used to promote social participation and the dynamics between City Hall and private companies. To observe the indicative elements of capacity building, the research used the policy capacity analysis model proposed by Ramesh et. al. (2016), focusing on the organizational and systemic levels. From the analysis of program documents (plans, minutes, contracts, among others), interviews with key actors involved in governance and affected residents, it was possible to conclude that the arrangement and its instruments provided municipal management with the capacities necessary for the level of intensity of participation foreseen for the program, which is limited to sharing information and consulting the affected population (ARNSTEIN, 1969; PAUL, 1987). On the other hand, the formulation of the program remained restricted to managers, in a typically managerial governance model (PIERRE, 2011). Therefore, without ensuring communities' access to the decision-making and formulation process, the institutional arrangement and its instruments were insufficient to mitigate conflicts and promote the empowerment of territories.